Indicators related to the rational use of medicines and its associated factors - Lima, Marina Guimarães; Álvares, Juliana; Guerra Junior, Augusto Afonso; Costa, Ediná Alves; Guibu, Ione Aquemi; Soeiro, Orlando Mario; Leite, Silvana Nair; Karnikowski, Margô Gomes de Oliveira; Costa, Karen Sarmento; Acurcio, Francisco de Assis (Revista de Saúde Pública, 2017)
OBJECTIVE: To evaluate indicators related to the rational use of medicines and its associated factors in Basic Health Units. METHOD: This is a cross-sectional study carried out in a representative sample of Brazilian cities included in the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015). The data were collected by interviews with users, medicine dispensing professionals, and prescribers; and described by prescription, dispensing, and health services indicators. We analyzed the association between human resources characteristics of pharmaceutical services and dispensing indicators. RESULTS: At national level, the average number of medicines prescribed was 2.4. Among the users, 5.8% had antibiotic prescription, 74.8% received guidance on how to use the medicines at the pharmacy and, for 45.1% of users, all prescribed medicines were from the national list of essential medicines. All the indicators presented statistically significant differences between the regions of Brazil. The dispensing professionals that reported the presence of a pharmacist in the unit with a working load of 40 hours or more per week presented 1.82 more chance of transmitting information on the way of using the medicines in the dispensing process. CONCLUSION: The analysis of prescription, dispensing, and health services indicators in the basic health units showed an unsatisfactory proportion of essential medicines prescription and limitations in the correct identification of the medicine, orientation to the patients on medicines, and availability of therapeutic protocols in the health services